An inquiry into good hospital governance: A New Zealand-Czech comparison - Štrach Pavel; Ditzel Elizabeth; Pirozek Petr (BMC, 2006)
Abstract Background This paper contributes to research in health systems literature by examining the role of health boards in hospital governance. Health care ranks among the largest public sectors in OECD countries. Efficient governance of hospitals requires the responsible and effective use of funds, professional management and competent governing structures. In this study hospital governance practice in two health care systems - Czech Republic and New Zealand - is compared and contrasted. These countries were chosen as both, even though they are geographically distant, have a universal right to 'free' health care provided by the state and each has experienced periods of political change and ensuing economic restructuring. Ongoing change has provided the impetus for policy reform in their public hospital governance systems. Methods Two comparative case studies are presented. They define key similarities and differences between the two countries' health care systems. Each public hospital governance system is critically analysed and discussed in light of D W Taylor's nine principles of 'good governance'. Results While some similarities were found to exist, the key difference between the two countries is that while many forms of 'ad hoc' hospital governance exist in Czech hospitals, public hospitals in New Zealand are governed in a 'collegiate' way by elected District Health Boards. These findings are discussed in relation to each of the suggested nine principles utilized by Taylor. Conclusion This comparative case analysis demonstrates that although the New Zealand and Czech Republic health systems appear to show a large degree of convergence, their approaches to public hospital governance differ on several counts. Some of the principles of 'good governance' existed in the Czech hospitals and many were practiced in New Zealand. It would appear that the governance styles have evolved from particular historical circumstances to meet each country's specific requirements. Whether or not current practice could be improved by paying closer attention to theoretical models of 'good governance' is debatable.